1993
DOI: 10.1002/ar.1092360307
|View full text |Cite
|
Sign up to set email alerts
|

Why do spermatozoa of American marsupials form pairs? A clue from the analysis of sperm‐pairing in the epididymis of the grey short‐tailed opossum, Monodelphis domestica

Abstract: In order to understand the evolutionary significance of sperm-pairing in American marsupials, an ultrastructural investigation was made of this process in the South American grey short-tailed opossum, Monodelphis domestica. One epididymis from each animal (5) was fixed for light and electron microscopy and divided into 18 segments. The contralateral tract was divided into similar segments and assessments made of the total number of spermatozoa and the proportion of sperm-pairs. The mean total sperm number was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 20 publications
0
19
0
2
Order By: Relevance
“…Esse fenômeno provavelmente ocorre em todos marsupiais americanos (Biggers & Creed 1962, Biggers et al 1964, Biggers 1966, exceto no Dromiciops australis (Temple-Smith 1987), mas não é observado em espécies australianas (Biggers et al 1964, Harding et al 1979, Barbour 1977, Temple-Smith 1984, Taggart et al 1993.O processo de maturação espermática nos marsupiais é mais evidente e complexo que nos outros grupos de mamíferos. Durante a passagem dos espermatozóides pelo epidídimo, eles apresentam modificações estruturais da maturação espermática (Temple-Smith & Bedfort 1976, Cummins et al 1986, Temple-Smith1984, Lin & Rodger 1999.…”
Section: Discussionunclassified
“…Esse fenômeno provavelmente ocorre em todos marsupiais americanos (Biggers & Creed 1962, Biggers et al 1964, Biggers 1966, exceto no Dromiciops australis (Temple-Smith 1987), mas não é observado em espécies australianas (Biggers et al 1964, Harding et al 1979, Barbour 1977, Temple-Smith 1984, Taggart et al 1993.O processo de maturação espermática nos marsupiais é mais evidente e complexo que nos outros grupos de mamíferos. Durante a passagem dos espermatozóides pelo epidídimo, eles apresentam modificações estruturais da maturação espermática (Temple-Smith & Bedfort 1976, Cummins et al 1986, Temple-Smith1984, Lin & Rodger 1999.…”
Section: Discussionunclassified
“…1I). Sperm pair inside the male by aligning their morphologically adapted heads precisely and fusing together (Taggart et al 1993). Phillips (1970) suggested that the function of sperm pairing in marsupials might offer protection for the acrosome during the passage through the male and female reproductive tracts.…”
Section: Empirical Evidence For Sperm Cooperationmentioning
confidence: 99%
“…The eupyrene spermatozoa are known to be essential for fertilization [Kennedy and Keegan, 1992], but the function of the apyrene spermatozoa remains obscure. Conjugated spermatozoa have been described from four or five animal groups; American marsupials [Biggers and Creed, 1962;Biggers and DeLamater, 1965;Phillips, 1972;Temple-Smith and Bedford, 1980;Taggart et al, 1993], the snail family Turritella [Afzelius and Dallai, 1983], the primitive apterygote insect group Thysanura [Dallai and Afzelius, 1984], dytiscid water beetles Afzelius, 1985, 1987], and the diplopod myriapods [Reger and Fitzgerald, 1979]. These studies suggest the pairing is an adaptation for a more effective swimming capacity, although many other suggestions as to the function of the conjugated spermatozoa have been offered .…”
Section: Introductionmentioning
confidence: 95%